TRANSFORMASI HUKUM UNI EROPA TERKAIT PEMBENTUKAN HUKUM NASIONAL DI INGGRIS DALAM PERSPEKTIF HUKUM ORGANISASI INTERNASIONAL - Syaravina Lubis; Sutiarnoto Sutiarnoto; Jelly Leviza (Journal of USU International Law, 2014)
ABSTRACT Upheaval of a country's economy is one of the reason of formation of an international organization, namely the European Union. The objectives of the European Union itself are to promote throughout the community a harmonious development of economic activities, a continuous, balanced expansion, an increase in stability, an accelerated raising of standard of living, quality of life and closer relation between states. This research has a problem formulation that consist the transformation of EU Law into law in member countries of the European Union, EU Law transformation in the UK, and the challenge as a legal action related to the transformation of EU law in the UK according to the International Organizations Law. This reasearch uses a normative research method. The results of the research on the transformation of EU law into national law of the member states are forming Regulations, Directives, Decisions shall be applied in the member states. EU law has supremacy to override national law of member states. Transformation of EU law in the UK was began with the European Communities Act 1972 agreement that was Britain ratification over EU law. Challenge as a legal action related to the transformation of EU law in the UK allowed under Article 230 and 232 EU Treaty, within filing a complaint to the national courts in accordance with a predetermined time to carry out the challenge, the challenge actions can be end up with an amendment. In conclusion, the transformation law in the EU member states in the form of Regulations, Directives and Decisions. Transformation of EU law in the UK is regulated through the European Communities Act 1972. Challenge as a legal action related to the transformation of EU law in the UK is allowed in order to create a better implementation. Advices related to this research are the transformation of EU law must be ensured that has been implemented as it should. Transformation of EU law in the UK should be ensured that EU law can overriding British National Law in case of conflict with EU law that is directly effective. Talks in depth, ask opinions of representatives of each member state in order to reach unity for ease of implementation of EU law in member states as well as minimize the action of challenge against EU law. Keywords : European Union, Law Transformation, Challenge.